Urticaria due to mefenamic acid intake – a case report - Gowthaman, Sneha; Dhandapani, C. (International Journal of Basic & Clinical Pharmacology, 2025)
Urticaria, or hives, is a condition of the skin involving abnormality of redness and swelling caused by excess accumulation of fluid, and may happen because of infection, drugs, food, psychogenic causes or respiratory allergens, but is occasionally idiopathic. The following report concerns a case where urticaria was secondary to the consumption of mefenamic acid. A 44-year-old woman reported generalized itch, rashes of the skin, giddiness, and two instances of vomiting after taking mefenamic acid 250 mg during menstrual pain. Her medical history included irregular menstrual periods, adenomyosis, fibroid uterus which was treated with an Mirena device at the age of 8 months, and uncontrolled diabetes. Lab tests revealed that IgE (548.1 IU/ml) and glycated haemoglobin (HbA1C) (11.0) were high. She was diagnosed with urticaria and diabetes mellitus and treated with hydrocortisone, antihistamines, insulin and supportive therapy, which led to the disappearance of symptoms and discharge in stable conditions. The case also shows that unmonitored use of mefenamic acid can cause severe hypersensitivity and is more likely in patients with comorbidities and the use of pharmacovigilance, medical awareness, responsible prescribing, and patient education can be used to prevent adverse drug reactions and ensure safe medication practices with the vulnerable population.